Analysis of the hamstring muscle activation during two injury prevention exercises - Monajati, A.; Larumbe-Zabala, E.; Goss-Sampson, M.; Naclerio, F. (Journal of Human Kinetics, 2017)
The aim of this study was to perform an electromyographic and kinetic comparison of two commonly used hamstring eccentric strengthening exercises: Nordic Curl and Ball Leg Curl. After determining the maximum isometric voluntary contraction of the knee flexors, ten female athletes performed 3 repetitions of both the Nordic Curl and Ball Leg Curl, while knee angular displacement and electromyografic activity of the biceps femoris and semitendinosus were monitored. No significant differences were found between biceps femoris and semitendinosus activation in both the Nordic Curl and Ball Leg Curl. However, comparisons between exercises revealed higher activation of both the biceps femoris (74.8 ± 20 vs 50.3 ± 25.7%, p = 0.03 d = 0.53) and semitendinosus (78.3 ± 27.5 vs 44.3 ± 26.6%, p = 0.012, d = 0.63) at the closest knee angles in the Nordic Curl vs Ball Leg Curl, respectively. Hamstring muscles activation during the Nordic Curl increased, remained high (>70%) between 60 to 40° of the knee angle and then decreased to 27% of the maximal isometric voluntary contraction at the end of movement. Overall, the biceps femoris and semitendinosus showed similar patterns of activation. In conclusion, even though the hamstring muscle activation at open knee positions was similar between exercises, the Nordic Curl elicited a higher hamstring activity compared to the Ball Leg Curl.